A three dimensional N-doped graphene/CNTs/AC hybrid material for high-performance supercapacitors. Issue 11 (20th January 2017) - Liu, Zi-Ang; Tao, Yuxi; Song, Xue-Zhi; Bao, Ming; Tan, Zhenquan
Abstract : Single walled carbon nanotubes and activated carbon intercalated N-doped graphene hybrid material was successfully fabricated and exhibited high performance as a supercapacitor. Abstract : How to improve the specific capacitance of electrode materials is of great research interest because it is a key factor for electrochemical capacitors. Herein we report a N-doped graphene/CNTs/AC (NGCA) mesoporous hybrid nanomaterial with three dimensional highly-dispersed structure synthesized by hydrothermal method. This NGCA hybrid nanomaterial has a high specific area of 952.92 m 2 g −1, due to its mesoporous structure caused by inserted carbon nanotubes (CNTs) and activated carbon (AC), preventing the agglomeration of N-doped graphene (NG). The specific capacitance of this materials reaches 750 F g −1 at 0.5 A g −1 in KOH (1 M), which is attributed to the path of ion transport supported by the CNTs, the packing density of the electrode being elevated by the AC, and the synergistic effect among layered AC, CNTs and NG. In addition, the stable hybrid architecture makes significant contributions to the superior cycle stability with 81% capacitance retention after 2000 charge and discharge cycles at a current density of 5 A g −1 . The easy synthesis and the superior electrochemical properties endow the hybrid material with great potential in green energy storage systems in the future.